Linear Maps Preserving Idempotency of Products of Matrices on Upper Triangular Matrix Algebras (Communications in Mathematical Research, 2021)
Let $\mathcal{T}_n$ be the algebra of all $n × n$ complex upper triangular matrices. We give the concrete forms of linear injective maps on $\mathcal{T}_n$ which preserve the nonzero idempotency of either products of two matrices or triple Jordan products of two matrices.